2003
DOI: 10.1016/s0378-1097(03)00470-1
|View full text |Cite
|
Sign up to set email alerts
|

Conversion ofShigella flexneriserotype 2a to serotype Y in a shigellosis patient due to a single amino acid substitution in the protein product of the bacterial glucosyltransferasegtrIIgene

Abstract: Conversion of serotype from 2a to Y was demonstrated with five Shigella flexneri isolates recovered from an infected patient. When introduced into the serotype Y isolate, the glucosyltransferase (gtr) II gene of the serotype 2a isolate is capable of inducing the conversion from serotype Y to 2a. In contrast, the gtrII of the serotype Y isolate lacks the capacity to change serotype, resulting from a CysCTyr substitution in its predicted protein sequence. The protein product of the gtrII gene was detected. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Each pair of primers obtained the predicted amplification product, which were 782 bp (wzx [1][2][3][4][5] ), 1,122 bp (gtrI), 518 bp (gtrIC), 1,272 bp (gtrII), 604 bp (oac), 378 bp (gtrIV), 905 bp (gtrV), and 425 bp (gtrX). The identity of each product was further confirmed by DNA sequencing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each pair of primers obtained the predicted amplification product, which were 782 bp (wzx [1][2][3][4][5] ), 1,122 bp (gtrI), 518 bp (gtrIC), 1,272 bp (gtrII), 604 bp (oac), 378 bp (gtrIV), 905 bp (gtrV), and 425 bp (gtrX). The identity of each product was further confirmed by DNA sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…Serotype Y strains carrying a defective gtrII gene have been reported previously. One case was an insertion sequence disruption of gtrII, while another was a single amino acid residual change leading to an inactive GtrII (5,14). The higher number of gtrII mutations found in serotype 2a and 2b S. flexneri strains may be due to a higher proportion of these serotypes in nature.…”
Section: Vol 49 2011 New Multiplex Pcr Assay For Serotyping S Flexmentioning
confidence: 99%
See 2 more Smart Citations
“…Roborts et al [27] found that the serotype Y vaccine candidate SFL124 contained an insertion sequence (IS1) in the gtrII gene, resulting in a nonfunctional GtrII. Chen et al [28] also observed the conversion of serotype 2a to serotype Y due to a single base mutation in gtrII which led to a Cys (437) to Tyr substitution. In our previous study [25], we have identified four serotype Y and two serotype X isolates carrying a defective gtrII gene, with one having a four-base deletion (bases 1197 to 1282) and five having a single base deletion (base 1031 or 1024).…”
Section: Resultsmentioning
confidence: 97%